Terapi SEFT (Spiritual Emotional Freedom Technique) Meningkatkan Regulasi Emosi Pada Anak Tunagrahita: SEFT (Spiritual Emotional Freedom Technique) Therapy Improves Emotional Regulation in Children with Mental Disabilities - Putri Intan Rosita Dewi; Anny Rosiana Mashitoh; Muhamad Jauhar (LPPM STIKES Guna Bangsa Yogyakarta, 2026)
Background: Children with intellectual disabilities often experience difficulty managing their emotions due to intellectual limitations, which can impact their mental health. SEFT (Spiritual Emotional Freedom Technique) therapy, which combines tapping techniques on the body's energy points with a spiritual approach, can improve emotional regulation. Objective: This study aims to analyze the effect of SEFT therapy on emotional regulation in children with intellectual disabilities. Methods: The study design used a quasi-experimental pre-test and post-test with a control group. The study was conducted in two special needs schools (SLB) in Kudus Regency in February 2025, with a sample of 38 students using a purposive sampling technique. Inclusion criteria were students with mild to moderate intellectual disabilities aged 7–15 years. Exclusion criteria included severe behavioral disorders, inhibiting conditions, and failure to complete the intervention. SEFT therapy was conducted in four sessions over two weeks, each lasting 15–20 minutes. The research instrument used the Emotion Regulation Checklist, and data analysis used paired t-tests and independent t-tests. Results: SEFT therapy significantly improved emotional regulation in children with intellectual disabilities (p=0.001). Conclusion: SEFT therapy effectively improves emotional regulation and is recommended for use in special education settings.